2010
DOI: 10.1007/s00420-010-0522-6
|View full text |Cite|
|
Sign up to set email alerts
|

National estimates of blood lead, cadmium, and mercury levels in the Korean general adult population

Abstract: This biomonitoring study of blood heavy metals in the Korean general population as part of KNHANES III provides important reference data stratified by demographic and lifestyle factors that will be useful for the ongoing surveillance of environmental exposure of the Korean general population to heavy metals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
38
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 97 publications
(47 citation statements)
references
References 64 publications
(81 reference statements)
6
38
3
Order By: Relevance
“…The geometric mean of the blood mercury concentration in this study was 3.42 µg/L. This finding is lower than that of other previous Korean studies [42526] but higher than that of previous reports from the United States and Canada [272829]. Fish consumption is one of major causes of mercury exposure [30], and fish and seafood are one of the favorite foods in Korea, which may explain why the blood mercury concentrations of the participants in this study were higher than those of adults in the United States and Canada.…”
Section: Discussioncontrasting
confidence: 88%
“…The geometric mean of the blood mercury concentration in this study was 3.42 µg/L. This finding is lower than that of other previous Korean studies [42526] but higher than that of previous reports from the United States and Canada [272829]. Fish consumption is one of major causes of mercury exposure [30], and fish and seafood are one of the favorite foods in Korea, which may explain why the blood mercury concentrations of the participants in this study were higher than those of adults in the United States and Canada.…”
Section: Discussioncontrasting
confidence: 88%
“…Smoking is also known to increase blood lead levels (Berode et al 1991;Navas-Acien et al 2004), and the recent KNHANES III study also found that the GM of the blood lead level was significantly higher in smokers than in nonsmokers and past smokers (Kim and Lee 2011). Conversely, in the present study, the GM of blood lead level in nonsmokers was significantly lower than that in smokers and past smokers; whereas, no difference was found between the GMs of blood lead levels in smokers and past smokers.…”
Section: Discussioncontrasting
confidence: 50%
“…Although blood mercury level reflects recent mercury exposure, it is used widely for monitoring the mercury exposure of population at risk and for comparison with other populations. The Second National Human Exposure and Biomonitoring Examination of Mercury measured the exposure level of 2369 Koreans at 3.80 (3.66 to 3.93) µg/L, whereas the Third Korean Health Examination Survey found a level of 4.15 (3.94 to 4.36) µg/L in 1997 adults [16-18]. The geometric mean of blood mercury concentration in our study was 7.99 (7.60 to 8.40) µg/L, which was higher than the range of 3.80 to 4.15 µg/L in the previous Korean National Studies.…”
Section: Discussionmentioning
confidence: 99%
“…However, no study has evaluated the health effects of mercury exposure on the risk for cardiovascular disease in coastal areas. In Korea, research on mercury has been limited to evaluating the mercury exposure by region or investigating pathological mechanisms as heart rate variability [16-21]. Investigations in other countries have compared the cardiovascular disease risk of subjects with high and low level of mercury, although studies on factors that are intermediate between mercury levels and risk for cardiovascular disease are insufficient [22].…”
Section: Introductionmentioning
confidence: 99%